Green astaxanthin extraction using microwave and ultrasound pretreatments - Parisa Feizi; Yahya Maghsoudlou; Hoda ShahiriTabarestani; Seid Mahdi Jafari; Amir-Houshang Bahri (npj Science of Food)
Abstract In this study, ultrasonic- and microwave-assisted extraction was performed to recover astaxanthin (ASX) from samples of F. merguiensis shrimp and P. maeoticus Gammarus using three solvents: organic solvent, vegetable oil and ionic micro emulsion. The microemulsions were evaluated in terms of density, conductivity and particle size. The microemulsion had a density of 0.9715 g/cm3, a conductivity of 312 µSiemens and an average particle size of 15.8 nm. The results showed that for both samples, the ionic microemulsion solvent performed better in ASX extraction and the F. merguiensis shrimp produced more total carotenoids compared to the other sample. In both methods, the recovery efficiency of ASX increased with increasing amount of solvent. Ultrasonic-assisted extraction better preserved the structure and antioxidant properties of ASX, but the microwave method showed higher extraction efficiency.